Students’ technological skills and attitudes toward HyFlex learning: the mediating role of online self-regulated learning, blended learning perception, and preferred learning modes - Amiruddin, Amiruddin; Sunardi, Sunardi; Setialaksana, Wirawan (Frontiers in Education, 2024)
HyFlex Learning has been used and researched in colleges in developing countries. The main challenges in HyFlex adaptation in colleges are the technology-related variables. However, investigations on HyFlex and its factors are limited. The current study aimed to explore the effect of students' technological skills on their attitudes toward HyFlex learning using 738 Indonesian college students. The mediating roles of online self-regulated learning (SRL), perceptions of blended learning, and students' preferred learning modes were also investigated. The results of the structural equation modeling analysis show that students' technological skills have a significant effect on their attitude toward HyFlex learning. Mediation analysis revealed that student technological skills had an indirect significant effect on their attitude toward HyFlex learning; that is, online self-regulated learning, perceptions of blended learning, and online asynchronous and face-to-face learning preferences partially mediated the effect of student technological skills on their attitude toward HyFlex learning. PLS-SEM also showed that students' technological skills have a direct effect on their online selfregulated learning and perceptions of blended learning. Online self-regulated learning and perceptions of blended learning were also shown to have a direct effect on students' attitudes toward HyFlex learning. Commented [M04]: Response to reviewer#2 comment Commented [M01]: Response to reviewer#2 comment Commented [M02]: Response to reviewer#2 comment Commented [M03]: Response to reviewer#2 comment Commented [M05]: Response to reviewer#4 comment on research questions.Thank you for your valuable recommendation on research questions. However, we have found out that we may choose between stating the research questions or using theoretical framework/hypothesis. In this article, we use the second one.Response to reviewer#2 comment on technological skills. All "technological competence" has been shifted into "technological skills"